Effect of planting density and complementary irrigation on the morpho-phenology, yield, profitability, and efficiency of banana fertilization - Cedeño García, Galo (2020)
This research aimed to evaluate the effect of planting density and complementary irrigation on the morpho-phenology, yield, profitability, and efficiency of banana fertilization in the Carrizal River Valley, Ecuador. The treatments consisted of two production systems (irrigation and rainfed) and four planting densities (1500, 2000, 2500 and 3000 plants ha-1). The variables recorded were bunch weight (kg), fruit yield (boxes ha-1), net economic benefit (USD ha-1) and NPK agronomic efficiency. Supplementary irrigation increased production by 30%, compared to the rainfed system. The bunch weight was inversely proportional to the crop densities, while the fruit yield was proportional to the densities. The linear regression model showed an increase of 6.50 kg of fruit plant-1 with supplementary irrigation, while in rainfed the production was 4.99 kg of fruit plant-1, signaling a loss of 1.51 kg of fruit plant-1 due to lack of supplementary irrigation. The highest commercial yield and net economic benefit was 1398 boxes of fruit and 3665 USD ha-1, respectively, with 3000 plants ha-1 under supplementary irrigation.